2017
DOI: 10.1007/s00381-017-3483-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary intraventricular meningiomas in children—experience of two cases with review of literature

Abstract: Meningiomas are rare in the pediatric age group, more so in the intraventricular location. They arise in the lateral ventricles from the arachnoid cells contained within the choroid plexus, in the third ventricle from the velum interpositum and in the fourth ventricle from the choroids. These tumors are usually large and have an aggressive behaviour. Surgical management of intra-ventricular meningiomas is challenging because of their deep location, large size at presentation and increased vascularity. The auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…In this literature review, 13 PM patients from 7 authors (Table 3), representing 13% of a total of 99 patients from 16 out of 32 authors who provided information about the history of NF2, suggest a lower concomitant occurrence rate of NF2 in pediatric patients with cerebral meningioma as compared to some single research series such as by Santos et al [7] with 9 patients, Muley et al [6] with 2 patients, and Chohan et al [29] with only 1 patient, suggesting an NF2 rate of 33%, 50%, and 100%, respectively.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In this literature review, 13 PM patients from 7 authors (Table 3), representing 13% of a total of 99 patients from 16 out of 32 authors who provided information about the history of NF2, suggest a lower concomitant occurrence rate of NF2 in pediatric patients with cerebral meningioma as compared to some single research series such as by Santos et al [7] with 9 patients, Muley et al [6] with 2 patients, and Chohan et al [29] with only 1 patient, suggesting an NF2 rate of 33%, 50%, and 100%, respectively.…”
Section: Discussionmentioning
confidence: 81%
“…Intraventricular meningiomas arise from arachnoid cap cells embedded in the choroid plexus or from the tela choroidea and do not present any dural attachments [3][4][5]. Although intraventricular meningiomas are relatively frequent in pediatric patients, they are extremely rare in the third ventricle [6]. Studies have shown male predominance [1,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Важно отметить, что симптомы заболевания являются неспецифичными и, как правило, развиваются постепенно. Обычно заболевание манифестирует развитием общемозговой симптоматики, связанной с повышением внутричерепного давления и характерными для этого изменениями на глазном дне [9,14]. Вырастая до значительных размеров, опухоль может оказывать локальное воздействие, с которым связано появление очаговой неврологической симптоматики, развитие гемипареза, судорог и другой симптоматики.…”
Section: клинические проявленияunclassified
“…Менингиомы бокового желудочка составляют 0,5-4,5% всех внутричерепных менингиом. Внутри желудочков опухоли возникают из арахноидальных клеток, имеющихся в сосудистом сплетении желудочков головного мозга, а также в сосудистой основе полости промежуточного паруса [14,20]. Поэтому они чаще расположены в области треугольника бокового желудочка или tela choroidea четвертого желудочка [1].…”
unclassified